IS THE CHILDREN CGPA AFFECTED BY WORKING MOTHERS: ACROSS SECTIONAL STUDY OF STUDENTS IN LEBANESE UNIVERSITIES - Al-khoury, Pierre; Zein, Daoud Cheiboub; Saade, Randa (Archives of Business Research, 2018)
“The working mother” isn’t a new concept in the global market, so is balancing between home, children and work. A misconception in the world says that the academic performance of children is negatively affected when the mother is a “working mother”. However, the real scenario is different: working mothers are more sensitive to their children’s education, from their academic performance, to their achievement of higher grades and CGPA. Data was collected from the Lebanese working parents and convenience sampling is used to collect data. Three-hundred respondents response is analyzed and 96% academic participation is seen. Working mothers in early infant ages of their children showed less academic performance as compared to those mothers who stayed at home in same period. Bianchi, Robinson, and Milkie (2006) demonstrated that the employed mothers are creative and finds ways to spend and maintain interactional time with their children.